EFFECT OF SEEDS PRIMING AND SOWING DATES ON VIABILITY AND VIGOUR OF TWO SOYBEAN (GLYCINE MAX L.) SEEDS CULTIVARS : EFFECT OF SEEDS PRIMING AND SOWING DATES ON VIABILITY AND VIGOUR OF TWO SOYBEAN (GLYCINE MAX L.) SEEDS CULTIVARS (Iraqi Journal of Market Research and Consumer Protection, 2026)
A laboratory experiment was conducted during the seasons of 2023 and 2024 in the Seed Technology Laboratory, Department of Field Crops- College of Agricultural Engineering Sciences - University of Baghdad, using a Completely Randomized Design (CRD) according to factorial experiments with four replicates and three factors. The first factor was planting dates (1 june , 15 june and 1 july), the second factor was two soybean cultivars (Lee 74 and Shaimaa), and the third was seed priming treatments ( GA3  300 mg L-1 , KCl 30 g L-1, and seaweed extract 3 ml L-1, in addition to two control treatments: soaking in distilled water and dry seeds). The results showed the superiority of the June 15th planting date and achieved the highest average radicle length, plumule length, seedling dry weight, and seedling vigor index. The Shaimaa cultivar exhibited the highest average in all the mentioned traits above. The seed priming treatment with seaweed extract excelled in radicle length and seedling vigor index, while the KCl treatment outperformed in seedling dry weight and plumule length. Overall, the planting date of June 15th and the Shaimaa cultivar showed superiority, along with the seed priming treatment with seaweed extract.